Low spikes and low harmonic distortion multilevel inverter for induction motor implementation - Aboadla E.H.E.; Aznan K.A.; Tohtayong M.; Khan S.; Hannan M.A.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bridge circuits; Electric rectifiers; Harmonic analysis; Harmonic distortion; Induction motors; Modulation; Nonlinear equations; Power converters; Pulse width modulation; Voltage control; Cascade multilevel inverter; Electronic converters; Harmonic spikes; Modulation techniques; Multilevel inverter; Selective harmonic elimination; Selective harmonics eliminations; Total Harmonic Distortion (THD); Electric inverters